Functional Characterization of the Internal Symmetry of MRAP2 Antiparallel Homodimer - Wang, Meng; Pi, Linyu; Lei, Xiaowei; Li, Lei; Xu, Jing; Kuang, Zhe; Zhang, Cong; Li, Liang; Zhang, Chao (Frontiers in Endocrinology, 2021)
The melanocortin receptors are defined as a series of vital pharmaceutical targets to regulate neuronal appetite and maintain controllable body weight for mammals and teleosts. Melanocortin receptor accessory protein 2 (MRAP2) functions as an essential accessory player that modulates the surface translocation and binding to a variety of endogenous or synthetic hormones of central melanocortin-4 receptor (MC4R) signaling. MRAP2 is a single-transmembrane protein and could form a functional symmetric antiparallel homodimer topology. Here, we inverted the N-terminal, transmembrane, and C-terminal domains and generated six distinct conformational variants of the mouse MRAP2 to explore the functional orientations and the internal symmetry of MRAP2 dimers. These remolded MRAP2 mutants showed proper assembly of the antiparallel homodimer and binding to the MC4R, but slightly altered the regulatory profile on the surface expression and the ligand-stimulated cAMP cascades of MC4R. This study elucidated the importance of the orientation of each domain of the single-transmembrane protein and revealed the pharmacological properties of the internal symmetry of the antiparallel homodimer for MRAP2.